Isolation, Identification, and Pathogenicity of Potential Probiotics Isolated from Intestinal Coconut Crab (Birgus latro Linnaeus, 1767) - Muhammad Aris; Tamrin Tamrin; Waode Munaeni; Sudirto Malan; Juharni Juharni; Rusmawati Labenua (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract